PENAMBAHAN KALSIUM PADA PAKAN UNTUK MENINGKATKAN FREKUENSI MOLTING LOBSTER AIR TAWAR (CHERAX QUADRICARINATUS) (CALCIUM ADDITION ON FOODS TO INCREASE FREQUENCY OF CHERAX QUADRICARINATUS MOULTING) - Rahman Hakim, Riza (Jurnal Gamma, 2009)
The purpose of this research is to know the effect of calcium addition on foods to frequency offreshwater lobster (Cherax quadricarinatus) moulting. This research has been done during 30 daysin Fisheries Indoor Laboratory, Faculty of Animal Husbandry and Fisheries, University ofMuhammadiyah Malang.Result of research shows that calcium addition on foods success to increase frequency offreshwater lobster moulting. It shown by treathment B (2%) which has highest moulting frequency1,47. Then followed by treathment D (6%) = 1,40, treathment A (0%) = 1,27, and treathment C (4%)= 1,13. Calcium addition on foods also give positive effect to survival rate and growth of freshwaterlobster. All of treathments were added by calcium show that they have higher survival rate valuethan other treathments were not by added calcium. The sequential data of the average of freshwaterlobster survival rate are treathment B (2%) = 93,33%, D (6%) = 93,33%, C (4%) = 86,67%, dan A(0%) = 80 %. Whereas the sequential data of average to growth of freshwater lobster are treathmentB (2%) = 0,85 g, D (6%) = 0,79 g, C (4%) = 0,78 g, dan A (0%) = 0,73 g.